PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE STAD DENGAN SOAL-SOAL PEMECAHAN MASALAH PADA MATA PELAJARAN MATEMATIKA DI SMA NEGERI 6 PALEMBANG - Indriati Indriati; Yusuf Hartono (Jurnal Pendidikan Matematika, 2011)
The clues of the research is to known description of students problem solving  ability by applying of Cooperative STAD type by problem solving . Model of study of cooperative STAD type by problem solving is a model to solve mathematics problem that have done by groups giving clues. The clues consist of some  solving keys that given a part, each of member groups get a key. Subject of reseach are 48 students of grade XI natural science in senior high school 6 Palembang. Data collecting have done by giving test that content 3 discription question. The results of analysis shown mean of discriptor indicator are 74.34%, average abilty are 79.04 or 85.42% have shown good ability for problem solving. Conclusions of this reseach are learning use study model of Cooperative Problem Solving could be done to practise the ability of student’s problem.Key word: the ability of  problem solving, model of study of Cooperative Type STAD by Problem Solving